Development of a Modular Power Converter - Stepanov, A.; Biesenieks, L.; Sokolovs, A.; Galkin, I. (Electrical, Control and Communication Engineering, 2009)
This report describes the most important details of elaboration of a versatile power module that can be utilized as a part of various converters. Two or more modules connected together can form a frequency converter or multilevel converter or 3-phase inverter/rectifier etc. Initially the module was developed for fast prototyping of uninterruptible power supplies and energy systems with alternative energy sources. The module can be used also as a basis for laboratory equipment of the power electronics course.